From Colonialism to Code - Nina Grünberger (Seminar.net)
There is currently a growing debate on the hegemonic power and ubiquity of IT monopolies and the implications of digital technologies in the context of education, especially media education. The debate is being conducted under the banner of digital capitalism and is mainly framed from the perspective of the Global North regarding the consequences of global developments for the 'West'. In the rare cases where a global, post- or decolonial perspective is adopted, social challenges such as inequalities are at the centre of the debate. These are framed in terms of the Global North exploiting the Global South through postcolonial dependencies, for example in the extraction of resources for technologies. This article goes beyond such perspectives. It outlines phenomena of digital capitalist power and domination in the context of education from a global, decolonizing perspective. The article primarily establishes a theoretical approach to the topic.